Follow-up of intracranial aneurysms treated by a WEB flow disrupter: a comparative study of DSA and contrast-enhanced MR angiography. (21st May 2015) - Mine, Benjamin; Tancredi, Illario; Aljishi, Ali; Alghamdi, Faisal; Beltran, Margarita; Herchuelz, Maxime; Lubicz, Boris
Abstract : Objective: To compare contrast-enhanced MR angiography (CE-MRA) and DSA for the follow-up of intracranial aneurysms (IAs) treated with the Woven EndoBridge embolization system DL (WEB DL; Sequent Medical, Aliso Viejo, California, USA). Materials and methods: We retrospectively identified all patients treated with a WEB DL between November 2010 and February 2013 in 2 hospitals. The IA occlusion was graded on follow-up CE-MRA and DSA by 4 independent readers and by 2 readers reaching a consensus, respectively. Interobserver agreement for MRA and intertechnique agreement was evaluated by calculating linear weighted κ. Results: Fifteen patients with 16 IAs were included. Mean delay between MRA and DSA was 2 months (range 0–16 months). Interobserver agreement for MRA was substantial to almost perfect (κ=0.686–0.921; mean κ=0.809). Intertechnique agreement was moderate to substantial (κ=0.579–0.724; mean κ=0.669). Only three out of five inadequately occluded IAs were detected by MRA. Conclusions: CE-MRA is a useful tool for the follow-up of IAs treated with a WEB DL. However, early follow-up with DSA remains mandatory to detect inadequately occluded IAs.